Formulasi Sediaan Gel Niosom Kafein dan Usaha Peningkatan Absorpsi melalui Kulit - Nafi'ah, Rahma; Darijanto, Sasanti Tarini; Mudhakir, Diky (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Cellulite is a condition in the skin that changes the topographic of the skin surface. Caffeine can be used as an active compound for its slimming effect. To improve the penetration into the skin and increasing its solubility for cellulite treatment, caffeine was formulated as niosome vesicles. Niosome was made by using thin layer hydration method. Span 60, caffeine and cholesterol dissolved in chloroform and evaporated to produse a thin layer. The dispersion of caffeine and niosome was formulated in the form of gel using 6% of HPMC gel base. To determine the formulation stability, caffeine niosome gel was stored at a room temperature and accelerated condition using climatic chamber at a temperature of 40⁰C, 75% RH for 28 days. The result was then compared with caffeine gel. The diffusion rate of both gels was determined in vitro using flow through method. The results showed that the niosome system improved the solubility of caffeine up to 20,34 mg/ml and also showed that the pH and viscosity of caffeine niosome gel were stable under room temperature and accelerated condition.The diffusion test showed that the flux of caffeine niosome gel is 13.991 μg/cm2Keywords : Caffeine, niosome, cellulite, diffusion test.